PERAN PENGUKURAN, STANDARDISASI, PENGUJIAN DAN JAMINAN MUTU (MSTQ) DALAM USAHA PENINGKATAN MUTU - Setyodewati Setyodewati (JURNAL STANDARDISASI, 2006)
Measurement, Standardization, Testing and Quality Assurance (MSTQ) have important role in the recent development of industry, science and technology. Those four elements are interrelated, thus are measurementwithout the accepted standard developed through National Standardization System is meaningless. Recently, most of calibration activities are carried out by private sector and their location are concentrated in Jakarta andWest Java. Most of them are focusing their calibration activities to the needs of their parent organizations, and the only small number of them also provides their calibration services to external customers. On the other hand, the number of testing laboratories increase faster as demand from the government for exported or imported products shall be tested by accredited testing laboratories as the application of mandatory national standards (SNI). Location testing laboratories widely spread in the country and their activities depend on the commodities of the region, for example, in the region those produce tea or coffee, there will be testing laboratories for tea and coffee. Scope of activities of calibration laboratories also focused on the measurement of mass, temperature, dimensional as most of Indonesian industries use the kind of measuring instruments for their processes.